Les limitations à la liberté de manifestation et d'association - Nadeau, Gaston (Les Cahiers de droit, 1978)
The Charter of Human Rights and Freedoms passed by the Legislature of Québec in 1975 suffers from major restrictions as to its scope. First, it is purely declaratory of existing freedoms, and does not purport to create new ones ; the Charter therefore only prevails on provincial statutes passed after it, and provided that such later acts do not specifically exclude the application of the Charter. Second, the Charter only applies to matters coming within provincial legislative power. Drawing the boundaries of any specific freedom therefore requires identification of the restrictions set upon it by both provincial legislation and federal jurisdiction. This paper attempts such a dedication of the fundamental rights of association and demonstration, set out in s. 3 of the Charter. Among matters coming within federal jurisdiction, the Criminal Code and the concept of national security are the main limitations on free association and demonstration. Provincial law on labour relations, trespass and private nuisance, the preservation of private property, and municipal regulation of nuisances, impose equally severe limitations.